2022
DOI: 10.1007/s13139-021-00730-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality Pattern of F-18 FDG PET Whole Body with Functional MRI Brain in Post-Acute COVID-19

Abstract: Purpose The study aimed to investigate imaging abnormalities associated with post-acute COVID-19 using F-18 FDG PET/CT and PET/ rsfMRI brain. Methods We retrospectively recruited 13 patients with post-acute COVID-19. The post-acute COVID-19 symptoms and neuropsychiatric tests were performed before F-18 FDG PET/CT whole body with PET/rsfMRI brain. Qualitative and semiquantitative analyses were also conducted in both whole body and brain images. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Concerning brain metabolism, there are no headache-specific studies, but the regions most frequently reported as hypometabolic include the right parahyppocampal gyrus [ 41 ], the brainstem, thalamus, amygdala [ 41 ], orbital gyrus, olfactory gyrus, and temporal lobe [ 42 ]. One study compared images from 18-fluor-deoxy-glucose PET and functional MRI imaging, showing an overlap between the areas where the connectivity was altered in the MRI and F-18 FDG PET changes [ 43 ]. Figure 1 summarizes the main mechanisms which could be involved in the long COVID headache pathophysiology.…”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%
“…Concerning brain metabolism, there are no headache-specific studies, but the regions most frequently reported as hypometabolic include the right parahyppocampal gyrus [ 41 ], the brainstem, thalamus, amygdala [ 41 ], orbital gyrus, olfactory gyrus, and temporal lobe [ 42 ]. One study compared images from 18-fluor-deoxy-glucose PET and functional MRI imaging, showing an overlap between the areas where the connectivity was altered in the MRI and F-18 FDG PET changes [ 43 ]. Figure 1 summarizes the main mechanisms which could be involved in the long COVID headache pathophysiology.…”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%
“…Brain metabolic changes have been documented across multiple studies of COVID-19 patients, although with inconsistent results [17,87]. Patterns of hypo-or hypermetabolism across different cortical and subcortical symptoms are related to neuropsychiatric symptoms of the disease, including anosmia [88], fatigue [89] and cognitive impairment [17].…”
Section: Discussionmentioning
confidence: 99%
“…Brain metabolic changes have been documented across multiple studies of COVID-19 patients, although with inconsistent results [23, 119, 120]. Patterns of hypo-or hypermetabolism across different cortical and subcortical symptoms are related to neuropsychiatric symptoms of the disease, including anosmia [121], fatigue [122] and cognitive impairment [23].…”
Section: Discussionmentioning
confidence: 99%